2010
DOI: 10.1007/s10238-010-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/beta-Catenin pathway in human glioma: expression pattern and clinical/prognostic correlations

Abstract: Gliomas are the most common primary intracranial tumors. Understanding the molecular basis of gliomas' progression is required to develop more effective therapies. The Wnt/β-catenin signaling cascade is an important signal transduction pathway in human cancers. Although, overactivation of this pathway is a hallmark of several forms of cancer, little is known about its role in human gliomas. Here, we aimed to determine the clinical significance of Wnt/β-catenin pathway components in gliomas. Immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
97
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 23 publications
(23 reference statements)
3
97
1
Order By: Relevance
“…In contrast, as presented in many studies, cytoplasmic accumulation is observed in a significantly higher proportion of malignant tumors than of normal or nonneoplastic tissue. 4,[26][27][28] This method of grouping actually revealed significant correlation between b-catenin and other markers such as cyclin D1, c-myc, APC, E2F1, p53, and MDM2, and tumor grade and patient survival. 4,26,27 The b-catenin expression in the cytoplasm and/or nucleus could be considered to be an indication of its aberrant expression.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In contrast, as presented in many studies, cytoplasmic accumulation is observed in a significantly higher proportion of malignant tumors than of normal or nonneoplastic tissue. 4,[26][27][28] This method of grouping actually revealed significant correlation between b-catenin and other markers such as cyclin D1, c-myc, APC, E2F1, p53, and MDM2, and tumor grade and patient survival. 4,26,27 The b-catenin expression in the cytoplasm and/or nucleus could be considered to be an indication of its aberrant expression.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, the reduced level of WIF1 protein expression, more frequent cytoplasmic or cytoplasmic/nuclear b-catenin staining pattern, and increased cyclin D1 and c-myc expression in glioblastomas relative to diffuse astrocytomas were consistent with results of other studies. 2,4,7,25 These findings suggest that WIF1 promoter methylation is a common process that occurs relatively upstream in tumorigenesis, and that the accumulation of additional downstream alterations in the WNT/b-catenin pathway is related to the aggressiveness of astrocytoma.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations